Candida antarctica Lipase B Synthetic Gene: A Bioinformatics Analysis - Febriana Dwi Wahyuni; seprianto Seprianto (UNIVERSITAS NEGERI PADANG, 2018)
Enzyme exploration is important to support the development of biotechnology. To facilitate microbial discovery, it can be done synthetically using bioinformatics methods. Candida antarctica lipase B (CALB) is one of enzyme derived from microorganisms and has been applied as a biocatalyst in several industry. The methods used in this study are the analysis of gene structure using NCBI, analysis of protein CALB sequence using Uniprot, analysis of 3D protein structure using Swiss model, analysis primary design using primer3 and analysis of restriction sites using snapgene. The construction of synthetic calB gene obtained based on the results of the CalB gene sequence in geneBank using NCBI with access number Z30645.1. CalB gene wildtype is modified by adding several restriction enzyme (XhoI, XbaI, ClaI, and BglI), 6 Histags, and 2x stops codon and produce 1083 base pairs. CALB protein has 342 amino acids. Based on 3D structure, CALB protein has three molecules in common with one homotrimer ring that will encircle the double helix DNA. Primers used for calB gene amplification are CALB forward 5'-TCCCCAGTATCAGGTCCAAG-3 ' and CALB reverse 5'-GACACCTGAGGCTGAACGAT-3'.